Reduced El Niño variability in the mid-Pliocene according to the PlioMIP2 ensemble - A. M. Oldeman (Copernicus Publications, 2021)
The mid-Pliocene warm period (3.264–3.025 Ma) is the most recent geological period during which atmospheric CO2 levels were similar to recent historical values (∼400 ppm). Several proxy reconstructions for the mid-Pliocene show highly reduced zonal sea surface temperature (SST) gradients in the tropical Pacific Ocean, indicating an El Niño-like mean state. However, past modelling studies do not show these highly reduced gradients. Efforts to understand mid-Pliocene climate dynamics have led to the Pliocene Model Intercomparison Project (PlioMIP). Results from the first phase (PlioMIP1) showed clear El Niño variability (albeit significantly reduced) and did not show the greatly reduced time-mean zonal SST gradient suggested by some of the proxies.